2010
DOI: 10.1108/09526861011010677
|View full text |Cite
|
Sign up to set email alerts
|

Factors that prevent physicians reporting adverse events

Abstract: The study provides an understanding why physicians fail to report adverse events so that systems can be introduced and cultures developed, which make this easier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Underreporting of incidents has been well documented in medicine and is an ongoing issue in MRS as well . The various reporting requirements of the state jurisdictions within Australia also contribute to the underreporting of adverse events .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Underreporting of incidents has been well documented in medicine and is an ongoing issue in MRS as well . The various reporting requirements of the state jurisdictions within Australia also contribute to the underreporting of adverse events .…”
Section: Discussionmentioning
confidence: 99%
“…James Reason, the esteemed author in the field of human error, argues that for error reporting to make a meaningful contribution to safety the culture of blame and culpability must be replaced with a reporting culture . The fear of blame and reprisals when reporting adverse events is well documented in medicine and may be a reason for underreporting in MRS. This is an area for possible further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, health care organizations often do not learn from failures, and this failure to learn is, at least in part, due to underreporting of errors and near misses by the frontline clinicians [ 6 ]. A number of factors have been identified that explain the low rates of error reporting including the belief that error reporting will not lead to safety improvements [ 7 , 8 ], confidentiality and legal concerns [ 9 ], a punitive work environment [ 10 ], traditions of professional autonomy [ 6 ], perfectionism [ 7 , 11 ], power hierarchies within and between professional groups [ 10 , 12 , 13 ], and poorly designed reporting systems [ 8 , 14 ]. While it is important for health care organizations to take steps to increase the rates of error reporting, they must not lose sight of the fact that error reporting by itself can be counterproductive if it does not lead to error analysis and system improvements [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these organisational, situational and individual obstacles of voice, increasing efforts are undertaken to better understand and develop strategies against them (Gallagher et al, 2006; Moumtzoglou, 2010; Rosen et al, 2005). For instance, employer-sponsored voice practices (ESVPs) – such as critical incidence reporting systems (CIRSs) – have been adopted from other high-risk professions.…”
Section: Introductionmentioning
confidence: 99%